Face recognition in color space - Zhao, Tiansi (2015)
Face recognition is a technology that automatically identifies or verifies a person from a digital image. There is one of the most popular ways to achieve face recognition by selecting facial features from the image and a facial database has been considered as well as applied in this project. For the fast development of science and technology, and the amount applications of face recognition system like security systems, face recognition has attracted many researchers and engineers in the area of image processing, pattern recognition and computer vision. This is a big challenge for face recognition is the unclear knowledge of the human beings recognizing method. This means researchers need to find the reliable and discriminative features from the amount of face features in the face image, which has been enhanced by tools provided by machine learning technology. As the color information is unreliable, most face recognition techniques work on the grey level image, which is the first part or objective of this project. However, recent research shows that face recognition by including color information may enhance the recognition accuracy. So after the grey level research and get familiar with this technology, the main objective of this project is investigate the face recognition of various color spaces and compare its performance with that based on the grey level images to find the better way of face recognize processing.